2016
DOI: 10.1016/j.actatropica.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a joint human-porcine intervention package for Taenia solium control: Results of a pilot study from northern Lao PDR

Abstract: Following confirmation that a remote village of approximately 300 inhabitants in northern Lao PDR was hyperendemic for the Neglected Tropical Disease Taenia solium, a pilot human-porcine therapeutic control intervention was implemented between October 2013 and November 2014. Mass drug administration with a three day albendazole 400mg protocol was offered to all eligible humans in October 2013 and March 2014. At these times, and again in October 2014, eligible village pigs received the anti-cysticercosis TSOL18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…We included 20 primary studies-reported across 33 articles-in the systematic review and excluded 221 (S3 File). For the 33 articles we identified 20 as the primary reference [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and 13 as supporting references [13,14,[54][55][56][57][58][59][60][61][62][63][64]. A source for the full text of some studies (n = 90) could not be found for assessment; 78% of these were published before 1990.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 20 primary studies-reported across 33 articles-in the systematic review and excluded 221 (S3 File). For the 33 articles we identified 20 as the primary reference [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and 13 as supporting references [13,14,[54][55][56][57][58][59][60][61][62][63][64]. A source for the full text of some studies (n = 90) could not be found for assessment; 78% of these were published before 1990.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these 10 studies also included selective chemotherapy of cases [34,35,39] and three tested MDA plus education [37,42,50]-with one of the intervention arms in the study by Steinmann et al also including construction of latrines [50]. One of the MDA interventions included education as well as vaccination and preventive chemotherapy in pigs [46]-thus the efficacy results cannot be attributed to the MDA but the outcomes related to side-effects, feasibility, and values and preferences can be used.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in prevalence and incidence of porcine cysticercosis was observed, but the effect of the intervention on prevalence of taeniosis was uncertain. In Laos, Okello et al [41] showed a significant drop in taeniosis prevalence following two annual albendazole MDA campaigns, and one pig vaccination and treatment campaign. No information on the effect on porcine cysticercosis was provided.…”
Section: Discussionmentioning
confidence: 99%
“…The recently reported results indicated that human MDA (2 g nicolsamide, three rounds per annum) administered in combination with porcine vaccination (TSOL18) and anthelmintic treatment (oxfendazole 30 mg/kg) successfully eliminated T. solium from the porcine intermediate host in 105 of 107 intervention villages, with elimination sustained for at least 1 year post-intervention 123. Recently in southeast Asia, porcine vaccination (TSOL18) and anthelmintic treatment (oxfendazole 30 mg/kg) have been combined with a human MDA program (two rounds triple-dose albendazole 400 mg) in Lao PDR, where an initial rapid reduction in human taeniasis prevalence was sustained over the 2 years of the study 49,54…”
Section: Multi-host Interventions Via a One Health Approach To Controlmentioning
confidence: 99%